Preparation method of electrified self-heating ceramic tile
By adding bacterial cellulose dry powder to the ceramic products and firing them at high temperature, carbon fiber is formed, giving the ceramic products conductivity and heating properties, and solving the problem that ceramic products cannot be heated with resistance, achieving a fast and controllable heating effect while maintaining the product. Other advantages.
Patent Information
- Application Number
- CN202310717193.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2024-12-17
AI Technical Summary
Due to the insulating properties of traditional ceramic products, it is difficult to meet the fast and controllable heating needs, especially when heating in winter, it is difficult to effectively heat up.
Bacterial cellulose dry powder is added to the mixed raw materials of the ceramic tile and converted into carbon fibers during the high-temperature firing process to form a conductive and heat-generating composite material, so that the ceramic products can be energized and self-heated at low voltage.
It has achieved the improvement of the electric heating performance of ceramic products, and can self-heat at low voltages to meet heating needs, while maintaining the advantages of the product, such as water absorption, damage strength and fracture module, which are basically unaffected, and are safe, energy-saving and environmentally friendly.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a ceramic tile, in particular to a method for preparing a ceramic tile capable of self-heating when powered on. Background Art
[0002] Ceramic tile is a kind of acid-alkali-resistant and porcelain or stone building or decorative material formed through grinding, mixing, pressing, glazing, sintering and other processes. According to the texture, it is mainly divided into porcelain tiles, ceramic tiles, etc.; according to the variety, there are polished tiles, antique tiles, ceramic tiles, full-glazed tiles, polished crystal tiles, etc.; according to the use, the common ones are floor tiles, wall tiles, etc. Ceramic tile products have many advantages such as strong water repellency and air permeability, acid and alkali resistance, freeze-thaw resistance, earthquake resistance, crack resistance, beautiful appearance, easy maintenance, etc., and are increasingly loved by consumers.
[0003] Winter heating, especially in northern my country, is mainly done by boiler heating. In addition, in southern my country, the unique wet and cold climate makes people uncomfortable, so the demand for winter heating is also increasing, but the heating time is short and scattered, and boiler heating, which is slow to heat, covers a large area, and needs to be maintained for a long time, is difficult to meet its heating needs.
[0004] Resistance heating is a method of electrically heating materials by using the thermal effect of electric current passing through a resistor. It has many advantages such as controllable and rapid temperature rise. If the material to be heated is used as a conductor in a circuit, the passage of current will also cause the material to heat up. However, since ceramics are insulators, they cannot be used as conductors in a circuit. Therefore, if ceramic products are to be able to achieve resistance heating, it is necessary to prepare ceramic composite materials to enhance their electrical conductivity and heating properties.
[0005] Bacterial cellulose (BC) is a natural cellulose raw material produced by natural bacterial fermentation metabolism. Compared with ordinary cellulose, it has extremely high purity, basically does not contain impurities such as lignin and hemicellulose, and has an ultra-fine three-dimensional spatial network structure, so it has excellent mechanical properties, and its production cost is low, the cycle is short, and it is environmentally friendly. It is a good natural biological raw material. Cellulose fibers will be carbonized into carbon fibers with conductive properties at high temperatures. Summary of the invention
[0006] The invention provides a method for preparing ceramic tiles capable of self-heating upon power-on, which comprises adding bacterial cellulose dry powder into ceramic tile mixed raw materials, mixing them evenly, and then firing them together at high temperature.
[0007] There is no special requirement for the source of bacterial cellulose hydrogel. Bacterial cellulose hydrogels prepared by various culture media and various bacterial fiber-producing bacteria can be used, but bacterial cellulose hydrogel products prepared by static fermentation are preferred. Before use, the bacterial cellulose hydrogel is preferably cleaned and purified, and conventional deionized water and weak alkaline solution cleaning and purification can be used.
[0008] The preparation method of the bacterial fiber dry powder in the present invention is not too limited, and various conventional drying methods can be used, but it is preferably prepared by vacuum freeze-drying and crushing the bacterial cellulose hydrogel after quick freezing. This is because the method of quick freezing combined with vacuum freeze drying will not destroy the three-dimensional spatial network structure inside the bacterial cellulose, and after high-temperature firing, such a structure can be maintained, which is conducive to obtaining better conductivity and heat generation performance.
[0009] More preferably, the quick freezing is to pre-cool the cleaned and purified bacterial cellulose hydrogel at 0-5°C, then quickly freeze it at a temperature below -18°C, and then perform vacuum freeze-drying.
[0010] In the present invention, the amount of bacterial cellulose dry powder added is 5-30% of the weight of the tile mixed raw material, which can be selected according to the conductivity and heating properties, and is preferably 10-20% of the weight of the tile mixed raw material.
[0011] The firing described in the present invention is high-temperature firing at 800-1400°C; preferably at 1100-1200°C; nitrogen can also be introduced for protection during firing.
[0012] The ceramic tile described in the present invention is one of indoor floor tiles, indoor wall tiles or indoor wall-floor integrated tiles.
[0013] The ceramic tile mixed raw material to which bacterial cellulose dry powder is added described in the present invention can be a mixed blank, a mixed glaze or both; there is no special requirement for the specific formula of the mixed blank or the glaze, but the mixed blank preferably includes: 25-45 parts of kaolin, 15-40 parts of clay, 10-20 parts of feldspar powder, 5-10 parts of quartz, and 1-3 parts of talc; the mixed glaze includes: 25-30 parts of quartz, 5-10 parts of dolomite, 6-18 parts of feldspar powder, 2-3 parts of borax, 1-3 parts of zinc oxide, and 5-10 parts of zircon.
[0014] The invention also provides a self-heating ceramic tile when powered on and prepared by the method.
[0015] The beneficial effects of the present invention are as follows: adding bacterial cellulose powder to the mixed ceramic tile blank, pressing and molding, and then firing at high temperature, the bacterial cellulose can be converted into carbon fibers and evenly distributed in the ceramic tile blank; or adding bacterial cellulose powder to the mixed glaze, and then firing at high temperature after glazing, the bacterial cellulose can also be converted into carbon fibers and evenly distributed in the ceramic tile glaze. The carbon fibers converted from the bacterial cellulose in the ceramic tile blank or glaze can maintain the fine mesh structure of the bacterial cellulose itself, and can form a composite material with electrical conductivity and heat generation after being combined with the ceramic tile material. The composite material can generate heat by itself when powered on at a very low human safety voltage, and can also easily realize heating control in different areas through circuit control. While maintaining the advantages of ceramic tile products, it can also meet the heating requirements in a safe, energy-saving and environmentally friendly manner. DETAILED DESCRIPTION
[0016] In order to better illustrate the present invention, we provide the following specific implementation modes. It should be noted that the following specific implementation modes are only for facilitating the understanding of the technical solutions of the present invention and shall not constitute any limitation to the present invention.
[0017] Example 1: Preparation of bacterial cellulose powder by hot air drying and crushing The bacterial cellulose hydrogel prepared by static shallow tray fermentation (coconut water culture medium, xylacetobacter xylinum, fermented at 28°C for 7 days) was purified by repeated washing with weak alkaline solution and deionization, dried with hot air at 45°C, and then pulverized through a 100-mesh sieve to obtain bacterial cellulose dry powder.
[0018] Example 2: Preparation of bacterial cellulose powder by vacuum freeze drying and pulverization The bacterial cellulose hydrogel prepared by static shallow tray fermentation (coconut water culture medium, xylacetobacter xylinum, fermented at 28°C for 7 days) was purified by repeated washing with weak alkaline solution and deionization, precooled at 5°C for 2h, then quick-frozen at -18°C for 10h, taken out and vacuum freeze-dried (-35°C, 0.6mbar) to constant weight, and then crushed through a 100-mesh sieve to obtain bacterial cellulose dry powder.
[0019] Example 3: Preparation of unglazed self-heating ceramic tiles Take 40 parts of kaolin, 30 parts of clay, 15 parts of feldspar powder, 6 parts of quartz and 2 parts of talc, mix them, add 35 parts of bacterial cellulose powder prepared in Example 1, stir and mix evenly, then slowly add appropriate amount of deionized water, continue stirring to form tile blanks, press them into shape, send them into a kiln, and sinter them at a high temperature of 1100°C (heating rate of 10°C / min, firing for 10h), during which N2 protection is introduced, and after completion, cool them to obtain unglazed self-heating tiles.
[0020] Example 4: Preparation of glazed self-heating ceramic tiles Take 35 parts of kaolin, 30 parts of clay, 10 parts of feldspar powder, 5 parts of quartz and 1 part of talc, mix them evenly, slowly add an appropriate amount of deionized water, continue to stir to form a tile blank, press it into shape, send it into a kiln, and sinter it at a high temperature of 1100°C (heating rate of 10°C / min, firing for 9h), pass N2 protection during the period, and cool it after completion; then take 30 parts of quartz, 8 parts of dolomite, 12 parts of feldspar powder, 3 parts of borax, 2 parts of zinc oxide, and 5 parts of zircon, mix them, add 20 parts of bacterial cellulose dry powder prepared in Example 2, stir and mix evenly, slowly add an appropriate amount of deionized water, continue to stir to form a tile glaze, brush the glaze on the cooled blank, and then put it into the kiln and fire it again at 1200°C (heating rate of 15°C / min, firing for 1.5h), pass N2 protection during the period, and cool it after completion to obtain a glazed self-heating tile.
[0021] Example 5: Preparation of self-heating ceramic tiles when powered on (heating of embryo and glaze at the same time) Take 25 parts of kaolin, 40 parts of clay, 12 parts of feldspar powder, 8 parts of quartz, and 3 parts of talc and mix them; add 25 parts of the bacterial cellulose powder prepared in Example 2, stir and mix evenly, slowly add an appropriate amount of deionized water, continue stirring to form a tile blank, press and form it, send it into a kiln, and sinter it at 1100°C (heating rate of 10°C / min, firing for 9h), during which N2 protection is introduced, and then cool it after completion; then take 30 parts of quartz, 8 parts of dolomite, 15 parts of feldspar powder, 2 parts of borax, 3 parts of zinc oxide, and 6 parts of zircon, mix them, add 18 parts of the bacterial cellulose powder prepared in Example 2, stir and mix evenly, slowly add an appropriate amount of deionized water to form a tile glaze, brush the glaze on the cooled blank, and then put it into the kiln and fire it again at 1250°C (heating rate of 15°C / min, firing for 1.5h), during which N2 protection is introduced, and then cool it to obtain an electric self-heating tile.
[0022] Experimental Example 1: Experiment on physical properties and electrical performance of ceramic materials 1) Preparation of comparative examples: Prepare the following comparative examples Comparative Example 3: Take 40 parts of kaolin, 30 parts of clay, 15 parts of feldspar powder, 6 parts of quartz and 2 parts of talc, mix them, stir them evenly, then slowly add an appropriate amount of deionized water and continue stirring to form a ceramic blank. After preparing it into a plate shape, send it into a kiln and sinter it at a high temperature of 1100°C (heating rate of 10°C / min, firing time of 9h). During this period, N2 protection is introduced. After completion, cool it to obtain unglazed tiles without adding bacterial cellulose dry powder.
[0023] Comparative Example 4: Take 35 parts of kaolin, 30 parts of clay, 10 parts of feldspar powder, 5 parts of quartz, and 1 part of talc, mix them, slowly add appropriate amount of deionized water, and continue to stir to form a ceramic blank. After preparing it into a plate shape, send it into a kiln and sinter it at a high temperature of 1100°C (heating rate of 10°C / min, firing for 9h), pass N2 protection during the period, and cool it after completion; then mix 30 parts of quartz, 8 parts of dolomite, 12 parts of feldspar powder, 3 parts of borax, 2 parts of zinc oxide, and 5 parts of zircon, stir and mix evenly, slowly add appropriate amount of deionized water, and continue to stir to form a ceramic glaze, brush the glaze on the cooled blank, and then put it into the kiln and fire it again at 1200°C (heating rate of 15°C / min, firing for 1.5h), pass N2 protection during the period, and cool it after completion to obtain glazed tiles without adding bacterial cellulose dry powder.
[0024] Comparative Example 5: Take 25 parts of kaolin, 40 parts of clay, 12 parts of feldspar powder, 8 parts of quartz, and 3 parts of talc, mix them, stir and mix them evenly, slowly add an appropriate amount of deionized water, and continue stirring to form a ceramic blank. After preparing it into a plate shape, send it into a kiln and sinter it at a high temperature of 1100°C (heating rate of 10°C / min, firing for 9h), pass N2 protection during sintering, and cool it after completion; then take 30 parts of quartz, 8 parts of dolomite, 15 parts of feldspar powder, 2 parts of borax, 3 parts of zinc oxide, and 6 parts of zircon, mix them, stir and mix them evenly, slowly add an appropriate amount of deionized water to form a tile glaze, brush the glaze on the cooled blank, and then put it into the kiln and fire it again at 1250°C (heating rate of 15°C / min, firing for 1.5h), pass N2 protection during the period, and cool it after completion to obtain glazed tiles without adding bacterial fiber dry powder.
[0025] 2) Determination of the effect of bacterial cellulose on the physical and chemical properties of ceramic materials The water absorption, breaking strength, and modulus of rupture of the samples were measured according to the test method in GB / T3810-2016 (the water absorption was measured using the vacuum method). The results are shown in the following table:
[0026] It can be seen from the experimental results that the addition of bacterial cellulose dry powder has almost no significant effect on the water absorption rate and rupture modulus of the composite tiles, and also improves the destructive strength of the product.
[0027] 3) Effect of bacterial cellulose on the electrothermal properties of ceramics Preparation of experimental samples: Crush the products in Example 3-5 and Comparative Example 3-5, select sample ceramic tiles with a smooth appearance and no obvious defects and cracks, and cut them into small discs with a diameter of about 5 cm using a cutting machine for later use.
[0028] i) Resistance experiment: Connect a 6V stable voltage to both ends of the composite tile disc, measure the resistance value at different times, and record it every 3 minutes. The results are shown in the table below:
[0029] From the above experimental results, it can be seen that in the initial stage after power-on, the resistance of the composite ceramic disc is significantly reduced, which may be due to the effect of the current breaking through the insulating layer. As the power-on time increases, the resistance of the composite ceramic material stabilizes at about 1.33. Since the bacterial cellulose powder directly dried by hot air is added in Example 3, its reticular structure may be destroyed during drying, and the fibers are prone to overlap and entanglement, making its resistance value relatively higher. Comparative Examples 3-5 without adding bacterial cellulose are insulators.
[0030] II) Temperature rise experiment: Connect a 6V stable voltage to both ends of the composite tile disc, measure the temperature value at different times, and record it every 5 minutes. The results are shown in the table below:
[0031] From the above experimental results, it can be seen that in the initial stage after power-on, the composite ceramic tile disc begins to heat up slowly, and the heating speed accelerates after 10 minutes. After 25 minutes, the temperature basically stabilizes and reaches above 55 degrees. Among them, the temperature of Example 4 is slower and the temperature is slightly lower, which should be because no bacterial cellulose is added to the blank, and it only relies on the glaze to heat up, and then conducts the heat to the entire ceramic material. The samples of Comparative Examples 3-5 without adding bacterial cellulose cannot heat up.
[0032] In summary, after the bacterial cellulose dry powder is added, it is carbonized to form carbon fibers during the firing process of the tile, which can give the tile product electrothermal properties without affecting the quality of the tile product and can provide excellent thermal effects at low voltage.
[0033] The embodiments described above are merely descriptions of preferred implementations of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary engineering and technical personnel in the field should all fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a self-heating ceramic tile when powered on. Features: Before high-temperature firing, the bacterial cellulose dry powder is added to the tile mixed raw materials and mixed evenly, and then fired at high temperature.
2. The method for preparing the self-heating ceramic tile when powered on according to claim 1, Features: The bacterial cellulose dry powder is prepared by quick-freezing the bacterial cellulose hydrogel, vacuum freeze-drying and pulverizing it.
3. The method for preparing the self-heating ceramic tile when powered on according to claim 2, Features: The quick freezing is to pre-cool the cleaned and purified bacterial cellulose hydrogel at 0-5°C and then quickly freeze it at a temperature below -18°C.
4. A method for preparing a self-heating ceramic tile when powered on according to any one of claims 1 to 3, Features: The amount of bacterial cellulose dry powder added is 15-45% by weight of the ceramic mixed raw material, preferably 30-35%.
5. The method for preparing the self-heating ceramic tile when powered on according to claim 4, Features: The firing is carried out at a high temperature of 800-1400°C; nitrogen is introduced during the firing for protection.
6. The method for preparing the self-heating ceramic tile when powered on according to claim 5, Features: The firing temperature is 1100-1200℃.
7. The method for preparing the self-heating ceramic tile when powered on according to claim 5, Features: The ceramic tile is one of indoor floor tiles, indoor wall tiles or indoor wall-floor integrated tiles.
8. The method for preparing the self-heating ceramic tile when powered on according to claim 1, Features: The ceramic tile mixed raw material is mixed blank material and / or mixed glaze material.
9. The method for preparing the self-heating ceramic tile when powered on according to claim 8, Features: The mixed blank comprises: 25-45 parts of kaolin, 15-40 parts of clay, 10-20 parts of feldspar powder, 5-10 parts of quartz, and 1-3 parts of talc; the mixed glaze comprises: 25-30 parts of quartz, 5-10 parts of dolomite, 6-18 parts of feldspar powder, 2-3 parts of borax, 1-3 parts of zinc oxide, and 5-10 parts of zircon.
10. A self-heating ceramic tile prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of bacterial cellulose based carbon nanofibers
CN103820883A
Composite carbon fiber heating ceramic tiles and preparation method thereof
CN109467410A
Method for manufacturing electrothermal functional ceramic through vacuumizing method, product and application method
CN110436903A
Biocellulose fiber, hemostatic dressing comprising said fiber and related application
WO2020220300A1
